Roles of telomeres and telomerase in age-related renal diseases - Li, Haili (Mol Med Rep, 2021)
Age-related renal diseases, which account for various progressive renal disorders associated with cellular and organismal senescence, are becoming a substantial public health burden. However, their aetiologies are complicated and their pathogeneses remain poorly understood. Telomeres and telomerase are known to be essential for maintaining the integrity and stability of eukaryotic genomes and serve crucial roles in numerous related signalling pathways that activate renal functions, such as repair and regeneration. Previous studies have reported that telomere dysfunction served a role in various types of age-related kidney disease through various different molecular pathways. The present review aimed to summarise the current knowledge of the association between telomeres and ageing-related kidney diseases and explored the contribution of dysfunctional telomeres to these diseases. The findings may help to provide novel strategies for treating patients with renal disease.